Multiple Myeloma Disrupts the TRANCE/Osteoprotegerin Cytokine Axis to Trigger Bone Destruction and Promote Tumor Progression - Pearse, Roger N.; Sordillo, Emilia M.; Yaccoby, Shmuel; Wong, Brian R.; Liau, Deng F.; Colman, Neville; Michaeli, Joseph; Epstein, Joshua; Choi, Yongwon (Proceedings of the National Academy of Sciences - PNAS, 2001)
Bone destruction, caused by aberrant production and activation of osteoclasts, is a prominent feature of multiple myeloma. We demonstrate that myeloma stimulates osteoclastogenesis by triggering a coordinated increase in the tumor necrosis factor-related activation-induced cytokine (TRANCE) and decrease in its decoy receptor, osteoprotegerin (OPG). Immunohistochemistry and in situ hybridization studies of bone marrow specimens indicate that in vivo, deregulation of the TRANCE-OPG cytokine axis occurs in myeloma, but not in the limited plasma cell disorder monoclonal gammopathy of unknown significance or in nonmyeloma hematologic malignancies. In coculture, myeloma cell lines stimulate expression of TRANCE and inhibit expression of OPG by stromal cells. Osteoclastogenesis, the functional consequence of increased TRANCE expression, is counteracted by addition of a recombinant TRANCE inhibitor, RANK-Fc, to marrow/myeloma cocultures. Myeloma-stroma interaction also has been postulated to support progression of the malignant clone. In the SCID-hu murine model of human myeloma, administration of RANK-Fc both prevents myeloma-induced bone destruction and interferes with myeloma progression. Our data identify TRANCE and OPG as key cytokines whose deregulation promotes bone destruction and supports myeloma growth.